The Implementation of Interactive Reading in Teaching Reading Comprehension at Twelfth-Grade Students of Senior High School Level - Irsyada, Fahmi; Dania, Rahma; Suparmi (English Education and Applied Linguistics Journal (EEAL Journal), 2024)
Reading is a crucial skill for academic and personal purposes, providing information and learning from texts. This study aimed to examine the effect of an interactive reading approach in improving students’ reading comprehension at 6th State Senior High School in Pariaman. The researcher used a pre-experimental one-group pretest-posttest design. The sample consisted of 32 students who received specific instruction on an interactive reading approach. Data collected from the pre and post-tests was analyzed using the Paired Sample T-Test in SPSS version 29. The paired sample test results showed a statistically significant difference between pre-test and post-test scores of -17, with a t-value of -15.830 and a p-value less than 0.001. This rejects the null hypothesis (H0) and accepts the alternative hypothesis (H1), indicating a significant difference between the two scores. This confirms that the learning intervention significantly improves students' reading comprehension, with an average difference of 17 points. Based on the result, the researcher suggests that the interactive reading approach can be an effective method for teaching reading to students, providing a more engaging lesson.